A continuum mechanics analysis of shear characterisation methods. (June 2018) - Akkerman, Remko
Abstract: The shear response of fabrics and fabric reinforced materials is primarily characterised by means of Picture Frame and Bias Extension experiments. Normalisation methods have been proposed earlier to enable comparison between different measurement results. Here, a continuum mechanics based analysis is presented for biaxial fabric materials without intra-ply slip, subject to constraints of fibre inextensibility. The fibre stresses are separated from the constitutively determined extra stresses, leading to a scalar equivalent stress resultant which makes the analysis of these tests more transparent. The equations are elaborated for both shear characterisation experiments and a direct measurement evaluation is proposed, without the need for iterative parameter identification methods.